Front Cover: Multitarget Compounds for Bipolar Disorder: From Rational Design to Preliminary Pharmacokinetic Evaluation (ChemMedChem 11/2020). (18th May 2020) - Di Martino, Rita Maria Concetta; Bottegoni, Giovanni; Seghetti, Francesca; Russo, Debora; Penna, Ilaria; De Simone, Alessio; Ottonello, Giuliana; Mandrup Bertozzi, Sine; Armirotti, Andrea; Bandiera, Tiziano; Belluti, Federica; Cavalli, Andrea
Abstract : The Front Cover summarizes the idea of developing molecules potentially active in the treatment of bipolar disorder, a mental condition in which episodes of mania alternate with depression. Within the framework of polypharmacology, the authors have rationally developed compounds that concurrently modulate two targets implicated in bipolar disorder: the dopamine receptor D3 and glycogen synthase kinase 3β. More information can be found in the Communication by Federica Belluti, Andrea Cavalli et al.